Analysis of “Code Blue” events in a single center: A cohort study with 419 incidents - Kocamer Şimşek, Betül; Akyılmaz, Ahmet Aykut (Journal of Surgery and Medicine, 2019)
Aim: Cardiac arrest sustains a significant cause of in-hospital morbidity and mortality worldwide and “Code Blue” (emergency code) is defined as a hospital code used to indicate a patient requiring immediate resuscitation. In this study we aimed to evaluate the ‘‘code Blue’’ events retrospectively in our hospital. Methods: Data were collected from the file book that is contained the patients’ name, protocol numbers, duration of arrivals to the arrest locale, final results of CPR and the CPR team’s names, locales of “code blue”. Patients’ gender, locales of “code blue”, false or right “code blue” situations, final results were analyzed. Results: One hundred-nineteen “code blue” situations were analyzed, 132 of 339 true “code blue” patients died at the locale after CPR. One hundred-forty four patients were transferred to reanimation unit, 29 were to the coronary intensive care unit (ICU), 28 were to the cardio-vascular surgery ICU, four were to pediatric-ICU and two were taken to the emergency operations. Also 113 of these 207 remaining patients were died in these units in later times, 94 patients survived. Eighty of them were determined as false code blue. Conclusions: Even the situation is in-hospital cardiac arrest and the CPR is performed by skilled team mortality rate may still be high. To prevent the false code blue situations, in-house training is indispensable for every hospital workers.